1986
DOI: 10.1007/bf00380762
|View full text |Cite
|
Sign up to set email alerts
|

A case-control study on the prognosis of vibration syndrome

Abstract: A case-control study was undertaken to evaluate some factors affecting the prognosis of vibration-induced white finger (VWF), 286 workers, who had used a chain saw in forests and had showed some symptoms and signs that were suspected to be vibration syndrome during some of the years from 1956 to 1980, were selected by medical examinations from a total of 612 forestry workers, and were divided into four groups according to the prognosis of the VWF based on a twenty-year follow-up. The study shows an association… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

1989
1989
2009
2009

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 6 publications
0
9
0
Order By: Relevance
“…On the other hand, Petersen et al (1995) mentioned that younger workers were at a disadvantage. Regarding smoking habits, some studies (Ekenvall and Lindblad 1989;Petersen et al 1995) demonstrated a positive relationship to VWF, while others (Brubaker et al 1986;Futatsuka and Sakurai 1986) indicated no association. As to complications, Petersen et al (1995) reported that vascular diseases had an unfavorable effect on the course of VWF, but Futatsuka and Sakurai (1986) found no such effect.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…On the other hand, Petersen et al (1995) mentioned that younger workers were at a disadvantage. Regarding smoking habits, some studies (Ekenvall and Lindblad 1989;Petersen et al 1995) demonstrated a positive relationship to VWF, while others (Brubaker et al 1986;Futatsuka and Sakurai 1986) indicated no association. As to complications, Petersen et al (1995) reported that vascular diseases had an unfavorable effect on the course of VWF, but Futatsuka and Sakurai (1986) found no such effect.…”
Section: Discussionmentioning
confidence: 95%
“…Futatsuka and Sakurai (1986) reported that older workers had a lower chance of improvement. On the other hand, Petersen et al (1995) mentioned that younger workers were at a disadvantage.…”
Section: Discussionmentioning
confidence: 96%
“…Studies have reported contrasting results about the role of tobacco consumption on the course of VWF and the cold response of digital arteries. No influence of smoking on either the progression of VWF in current users of vibratory tools or the reversibility of VWF in ex-users have been reported in longitudinal and case-control studies (Bovenzi et al 1998;Futatsuka and Sakurai 1986;Ogasawara and Sakakibara 1997). On the contrary, some follow up studies have suggested that smokers exposed to hand-transmitted vibration may have a poorer prognosis for VWF and coldinduced vasoconstriction than non-smokers (Cherniack et al 2000;Petersen et al 1995).…”
Section: Discussionmentioning
confidence: 89%
“…Consistently, these studies reported that the improvement in the cold response of digital arteries was more evident in non-smokers or ex-smokers than in current smokers, even though the beneficial effect on digital vascular function was not accompanied by improvement in subjective experience of finger blanching attacks (Cherniack et al 2000;Petersen et al 1995). On the contrary, other longitudinal and case-control studies have found no influence of smoking on either the progression of VWF in current users of vibratory tools or the reversibility of VWF in ex-users (Futatsuka and Sakurai 1986;Ogasawara and Sakakibara 1997). Similar results have been reported in a prospective study of the cold response of digital arteries in chain saw operators (Bovenzi et al 1998).…”
Section: Measures Of Vibration Exposure Fsbp% 10°l R Test (V 2 1df)mentioning
confidence: 85%